Credit Transfer System (CTS) Design in Academic Information System of Diponegoro University - Subari, Arkhan; Fauzi, Adnan (Journal of Vocational Studies on Applied Research, 2019)
One of the information system built in Diponegoro University is Academic Information System. This system manages every process and outcome of academic activities. Academic information system is developed to meet the needs of process and academic data that is also always growing. One of growing academic process is the implementation of Credit Transfer System (CTS). Credit Transfer System is an academic process whereby every Diponegoro University student can attend lectures in subjects that are interested without being tied to courses and curriculum. The realization is that every student can take a course or KRS interest in any study program in Undip. With the implementation of the CTS, the Academic Information System should be developed by adding new features to adopt the system. The application of CTS in academic information systems is done by adding a group of menus to the academic information system, offering CTS courses, creating a CTS lecture schedule, looking at college schedules, viewing and printing present CTS lectures, creating UTS and UAS schedules, printing UTS and UAS att